2014
DOI: 10.21608/jfds.2014.52982
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Beet Juice and Its Liquor During Beet Sugar Processing.

Abstract: This investigation was carried out to study the quality of beet juice and its liquors during beet sugar processing. Sample of sugar beet roots and slices were taken from the research fields of Delta sugar company. The samples of moist past, raw juice, clear juice, syrup and masscuites A, B and C were obtained from processes of Delta sugar factories during the 2013 working season. The samples were analyzed for the following: Moisture, ash, sucrose, total soluble solids, αamino nitrogen, sodium, potassium, purit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…Technological characteristics of fresh roots of four sugar beet varieties harvested at different periods: Table (2) showed that the technological characteristics of fresh roots of four varieties of sugar beet which have been grown at different times. White sucrose or sucrose recovery (SR) of four varieties harvested at three periods ranged between 8.76and 16.35% similar results were recorded by Al- Barbari et al (2014a) and Al-Barbari et al (2014b) who found that SR was ranged from 14.31 and 15.96%. Sucrose recovery depended on some factors such as sucrose, K and α-N content.…”
Section: Resultssupporting
confidence: 83%
“…Technological characteristics of fresh roots of four sugar beet varieties harvested at different periods: Table (2) showed that the technological characteristics of fresh roots of four varieties of sugar beet which have been grown at different times. White sucrose or sucrose recovery (SR) of four varieties harvested at three periods ranged between 8.76and 16.35% similar results were recorded by Al- Barbari et al (2014a) and Al-Barbari et al (2014b) who found that SR was ranged from 14.31 and 15.96%. Sucrose recovery depended on some factors such as sucrose, K and α-N content.…”
Section: Resultssupporting
confidence: 83%
“…Delaying harvest ages of sugar beet from 165 to 195 days caused the increase in quality of beet from 81.23 to 91.51% and from 79.20 to 88.62% in the 1 st and 2 nd seasons, respectively. The results are in agreement also with those reported by Gomaa ( 2009) and Al- Barbari et al (2014) who found that the quality of beet increased during the period of the beet processing. Such effect might be attributed to the increase in sugar recovery and pol percentages.…”
Section: Effect Of Harvesting Ages Of Sugar Beet Varieties On Beet Roots Quality During Two Seasonssupporting
confidence: 93%